Education leadership in changing learning environments: A view of the Catholic Social Teaching - Jada Pasquale Yengkopiong (Har Press Indonesia, 2023)
Leadership has always been an area of interest, and this cannot be less in education. In this study, the aim was to review and understand how education leaders safeguard the principles of the Catholic Social Teaching in the learning institutions. Through review of literature, it is shown that the current direction of industrialization and global exponential population growth is causing anxiety and distress in societies that want to keep the status quo. This behavior is a burden to societal wellbeing, and it is changing people in an unprecedented manner. The behavior challenges leaders at all levels, but more so, the education leaders in the learning institutions. The fear of population growth and knowledge explosion in societies that were less known for influencing global politics has led to the abuse of authority by those in leadership. The fear has also led to subjugation of members of minority groups into conditions that are ethically and morally in conflict with the principles of common good, human dignity, solidarity, subsidiarity, and stewardship according to the Catholic Social Teaching. In these principles, education leaders must afford equal opportunities to all racial, cultural, and social groups to learn and to lead.